1993
DOI: 10.2105/ajph.83.12.1746
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Borrelia burgdorferi and tick salivary gland proteins in New Jersey outdoor workers.

Abstract: In 1990, a second cross-sectional study of outdoor workers (n = 758) at high risk for Lyme disease was conducted. A questionnaire was administered, and antibodies to Borrelia burgdorferi and tick salivary gland proteins (antitick saliva antibody, a biologic marker of tick exposure) were assayed by enzyme-linked immunosorbent assay. The statewide Lyme disease seroprevalence increased from 8.1% in 1988 to 18.7% in 1990. Antitick saliva antibody seropositivity varied by county and was associated with measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Although the human response to tick bite may include intense cutaneous inflammation with accompanying histological changes, people often are unaware of having been bitten (1,5,9,20,(24)(25)(26). Quantitative biologic markers of tick exposure are needed to better understand the epidemiology, pathogenesis, immunology, and clinical manifestations of the human tick bite response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the human response to tick bite may include intense cutaneous inflammation with accompanying histological changes, people often are unaware of having been bitten (1,5,9,20,(24)(25)(26). Quantitative biologic markers of tick exposure are needed to better understand the epidemiology, pathogenesis, immunology, and clinical manifestations of the human tick bite response.…”
mentioning
confidence: 99%
“…One such marker may be host antibody directed against tick antigen. The frequency of exposure to Ixodes ticks can be determined using whole salivary gland extract derived from I. scapularis and a recombinant calreticulin antigen derived from Amblyomma americanum (20,(24)(25)(26). No previous studies have used an Ixodes recombinant antigen to test deer tick exposure or examined people whose antibody status could be measured before and more than a few months after tick exposure in order to determine antibody kinetics.…”
mentioning
confidence: 99%
“…4,5 Since 1991, investigations have suggested that anti-tick saliva antibodies are biologic markers of exposure to ticks. [6][7][8][9] For example, levels of anti-tick saliva antibody (ATSA), using sonicated whole Ixodes scapularis Say salivary glands as antigen, are associated with self-reported tick exposure, Lyme disease seroprevalence, and an index of tick engorgement. 7,10 The ATSA levels also decrease during periods of decreased tick exposure.…”
mentioning
confidence: 99%
“…Schwartz and others, who pioneered research into the use of anti-tick saliva antibodies as a biologic marker of tick exposure, [1][2][3][4][5] expressed similar concerns with the specificity of their AASA assay involving the ticks Ixodes dammini (now I. scapularis) and D. variabilis plus the mosquito A. aegypti. 1 In their initial assay, 1 all 3 antibodies to arthropods were intercorrelated and each of them was correlated with antibody titers to B. burgdorferi as well.…”
Section: 51mentioning
confidence: 99%
“…[1][2][3][4][5] In New Jersey, antibodies to salivary gland proteins of the vector tick Ixodes scapularis have been associated with measures of self-reported tick exposure (e.g., tick bites in the past year) among outdoor workers. Although problems with the specificity of the assay for certain ticks may limit its usefulness in some settings, 1 this technique holds considerable promise as an outcome measure in epidemiologic studies of the prevention of Lyme disease or other emerging tickborne infections, 6 and for identifying individuals or groups at high risk for such diseases.…”
mentioning
confidence: 99%